Neuropsychological deficits in patients with cognitive complaints after COVID‐19. Issue 3 (8th February 2022) - García‐Sánchez, Carmen; Calabria, Marco; Grunden, Nicholas; Pons, Catalina; Arroyo, Juan Antonio; Gómez‐Anson, Beatriz; Lleó, Alberto; Alcolea, Daniel; Belvís, Roberto; Morollón, Noemí; Mur, Isabel; Pomar, Virginia; et al.
Abstract: Background: While much of the scientific focus thus far has been on cognitive sequelae in patients with severe COVID‐19, subjective cognitive complaints are being reported across the spectrum of disease severity, with recent studies beginning to corroborate patients' perceived deficits. In response to this, the aims of this study were to (1) explore the frequency of impaired performance across cognitive domains in post‐COVID patients with subjective complaints and (2) uncover whether impairment existed within a single domain or across multiple. Methods: Sixty‐three patients with subjective cognitive complaints post‐COVID were assessed with a comprehensive protocol consisting of various neuropsychological tests and mood measures. Cognitive test performance was transformed into T scores and classified based on recommended guidelines. After performing a principal component analysis to define cognitive domain factors, distributions of test scores within and across domains were analyzed. Results: Results revealed pervasive impact on attention abilities, both as the singularly affected domain (19% of single‐domain impairment) as well as coupled with decreased performance in executive functions, learning, and long‐term memory. These salient attentional and associated executive deficits were largely unrelated to clinical factors such as hospitalization, disease duration, biomarkers, or affective measures. Discussion: These findings stress the importance of comprehensive evaluation and intervention to address cognitive sequelae in post‐COVID patients of varying disease courses, not just those who were hospitalized or experienced severe symptoms. Future studies should investigate to what extent these cognitive abilities are recuperated over time as well as employ neuroimaging techniques to uncover underlying mechanisms of neural damage. Abstract : This figure helps to visualize the frequency of deficits by cognitive domain. Additionally, it allows the reader to see what percentage of patients showed single‐domain versus multi‐domain cognitive impairment.